Effect of nanosilver on potato plant growth and protoplast viability - Ehsanpour, Ali Akbar; Nejati, Zeynab (Biological Letters, 2014)
Potato tissue culture is sensitive to ethylene accumulation in the culture vessel. Ag inhibits ethylene action but no information on nanosilver application in potato tissue culture has been published so far. In our study, potato cv. White Desiree was treated with nanosilver (0, 1.0, 1.5, and 2.0 ppm) in vitro. Leaf surface was increased, while stem length and root length decreased. Nanosilver caused also a decrease in the number of isolated protoplasts and in the viability of isolated protoplasts when applied either directly or indirectly.